Effect of COVID-19 pandemic on state funding of Polish football clubs - Kielbasinski, W.; Brzezinski, M. (Journal of Physical Education and Sport, 2021)
The financial crisis caused by the COVID-19 pandemic has affected professional football clubs. The suspensionof competitions, the lack of fans in the stands and the additional costs associated with the pandemic have affected the finances of football clubs. It should be emphasised that professional sports clubs are treated as enterprises engaged in economic activity. Some of them have received state aid under the so-called "Anti-CrisisShield". It should be pointed out that only selected clubs have received state aid due to their difficult financial situation. The support has been received by 11 out of 16 clubs playing in the Ekstraklasa in the 2020/2021 season. This is related, among other things, to the conditions of eligibility for the support. The total amount provided under the "Anti-Crisis Shield 1.0" amounts to PLN 25,044,742. The authors have also requested public information regarding the financing of Ekstraklasa football clubs by local government units in 2020 on the basisof the Act concerning free access to public information. The data for 12 selected football clubs has been compared with the information on funding for the selected clubs in 2019. On the basis of an analysis of the situation of the selected clubs, conclusions have been drawn regarding the impact of the financial crisis on the transfer of public funds to professional football clubs. It has been found that the financial crisis did not have amajor impact on the funding of several Ekstraklasa football clubs by local government units. In only a few cases did the clubs receive lower subsidies. Moreover, in several cases, the funding received in 2020 was higher thanin 2019. As part of the research, a survey has also been carried out in order to obtain answers to questions concerning the reasonableness of public financing of Polish football clubs. A total of 925 people took part in the survey. They answered closed and open questions. More than half of the people (51%) asserted that Polishprofessional football clubs should receive public funding from local government units. The opposite view washeld by 49% of the people who took part in the survey. The vast majority (91.4%) believed that the COVID-19 pandemic had had a negative impact on the financial situation of Polish professional football clubs. It also indicated what percentage of the losses of Polish professional football clubs should be compensated by the funds received under the 'Anti-Crisis Shield'